1994
DOI: 10.1093/rheumatology/33.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium Synovectomy in Haemophilic Arthropathy

Abstract: Between 1987 and 1991 we performed Yttrium-90 (Y-90) silicate radionuclide synovectomies on 40 joints of 20 haemophiliac patients with haemophilic arthropathy. All were male, their mean age was 31 yr and 15 of the 20 (75%) were HIV antibody positive. The number of joint bleeds and amount of factor (VIII and IX) replacement given in the 6 months pre- and 6 and 12 months post-radionuclide synovectomy was compared. Y-90 silicate synovectomy was shown significantly to reduce both the number of joint bleeds (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 0 publications
4
19
1
Order By: Relevance
“…This relatively low success rate might be explained with the high ratio of advanced disease in our patient group, as 10 out of 11 joints showed cartilage loss on pre-procedure MRI. There are reports indicating that the likelihood of a favourable response was higher in joints with no or little radiological damage, similar to the findings in patients with rheumatoid arthritis (10,11,12). It has been proposed that initial findings on MRI, in particular, measures of the severity of synovial hyperplasia, may be inversely related to clinical response to radiosynoviorthesis (13).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This relatively low success rate might be explained with the high ratio of advanced disease in our patient group, as 10 out of 11 joints showed cartilage loss on pre-procedure MRI. There are reports indicating that the likelihood of a favourable response was higher in joints with no or little radiological damage, similar to the findings in patients with rheumatoid arthritis (10,11,12). It has been proposed that initial findings on MRI, in particular, measures of the severity of synovial hyperplasia, may be inversely related to clinical response to radiosynoviorthesis (13).…”
Section: Discussionsupporting
confidence: 75%
“…This success rate is not as high as the previous studies which reported improvement from 75% to 90% after radiosynovectomy(2,3,4,5,6,7,8,9,10,11,33,34). This relatively low success rate might be explained with the high ratio of advanced disease in our patient group, as 10 out of 11 joints showed cartilage loss on pre-procedure MRI.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…This outcome is comparable to the previous reports which had a success rate ranged from 75% to 90% after radiosynovectomy with Y-90, Re-186, and other radionuclides in patients with hemophilia. [4][5][6][7][8][9][10][11][12]20 In this study, radiosynovectomy fails to control hemarthrosis in 13% of the joints (joints had less than 30% reduction in bleeding episodes or no chance). On the other hand, 3% of treated joints had moderate improvement, and 9% of treated joints had mild improvement.…”
Section: Discussionmentioning
confidence: 65%
“…10 In the hope of reducing complications, hospitalization, and cost, nonsurgical synovectomy using radionuclides in patients with hemophilia was first reported by Ahlberg et al 11 After that, there have been several studies concerning the usefulness and clinical success of this procedure. [12][13][14][15][16] It is generally accepted that radioactive synovectomy is safe, easily performed, requires low antihemophilic factor coverage, and can be carried out on an ambulatory basis. It is also reported that radiosynovectomy can be effective in reducing hemarthrosis frequency up to approximately 75% on average.…”
Section: Discussionmentioning
confidence: 99%